2009
DOI: 10.1590/s0103-84782009005000248
|View full text |Cite
|
Sign up to set email alerts
|

Soroepidemiologia da doença de Newcastle em plantéis de avestruzes dos Estados da Bahia e de São Paulo

Abstract: RESUMO Estudos sorológicos em Avestruzes (Struthio camelus) são ferramentas úteis para analisar os riscos relacionados à Doença de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…At Cacha Pregos the presented positivity can be related to the contact with migratory birds as well as to the acquisition of birds from the aviary pole of Feira de Santana, city near Cacha Pregos. The serologic research at backyard chicken breeding shacks and ostrich related by SALES (2007), FERNANDES et al (2009 and MATTOS (2013), at the Feira de Santana/Bahia region, showed the presence of antibodies against the Newcastle disease virus, even without any report of the birds' vaccination, strengthening the hypothesis that the birds got in contact with the virus (low-virulence strains), representing a risk factor for the poultry culture at the studied region. Nonetheless, the RT-PCR and viral isolation results were negative, proving that the birds were not eliminating the virus at the moment of sample collection.…”
Section: Discussionmentioning
confidence: 69%
“…At Cacha Pregos the presented positivity can be related to the contact with migratory birds as well as to the acquisition of birds from the aviary pole of Feira de Santana, city near Cacha Pregos. The serologic research at backyard chicken breeding shacks and ostrich related by SALES (2007), FERNANDES et al (2009 and MATTOS (2013), at the Feira de Santana/Bahia region, showed the presence of antibodies against the Newcastle disease virus, even without any report of the birds' vaccination, strengthening the hypothesis that the birds got in contact with the virus (low-virulence strains), representing a risk factor for the poultry culture at the studied region. Nonetheless, the RT-PCR and viral isolation results were negative, proving that the birds were not eliminating the virus at the moment of sample collection.…”
Section: Discussionmentioning
confidence: 69%
“…Many of these birds, being they migratory, wild or domestic, are natural hosts and transmit various infectious viruses, such as Influenza A, West Nile and Newcastle Disease (Fernandes et al, 2010, Flores & Weiblen, 2009.…”
Section: Introductionmentioning
confidence: 99%
“…The Newcastle Disease virus (NDV), which belongs to the family Paramyxoviridae and genus Avulavirus, has various pathogenic strains (Arns et al, 2007;Farkas et al, 2009;Fernandes et al, 2010). The history of Newcastle Disease began in 1926 with the description of a highly pathogenic disease in two geographical areas on opposite sides of the world, Newcastle-onTyne in England and the island of Java in Indonesia (Kraneveld, 1926;Doyle, 1927;Alexandre, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation